Implementation of the EU Enforcement Directive in the Baltic countries : experience in view of the development of protection of intellectual property rights - Janušauskaitė, Kristina (MIPLC studies ;, 2010)
How did the implementation of the EU Enforcement Directive on IP rights, which was adopted just before the expansion of the EU in May 2004, affect new EU Member States? This monograph is focused on three Baltic countries (Lithuania, Latvia and Estonia) and is aimed to present the collected information on the most relevant historic, social, economic and legal factors of those countries and to examine them. The examination leads to certain observations on what impact the listed factors made on the implementation of the Directive in that region, how they changed the "IP enforcement mechanisms", case practise which existed before the adoption of the Directive, and what IP right holders can expect when litigating in the Baltics. Besides, this monograph gives a bigger picture on what the aims and objectives of the Enforcement Directive were and how they were actually reflected in the current IP enforcement practice of the so-called countries in transit where effective enforcement of IP rights is essential